2013
DOI: 10.1124/dmd.112.048272
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Silymarin Flavonolignans with Organic Anion-Transporting Polypeptides

Abstract: Organic anion-transporting polypeptides (OATPs) are multispecific transporters mediating the uptake of endogenous compounds and xenobiotics in tissues that are important for drug absorption and elimination, including the intestine and liver. Silymarin is a popular herbal supplement often used by patients with chronic liver disease; higher oral doses than those customarily used (140 mg three times/ day) are being evaluated clinically. The present study examined the effect of silymarin flavonolignans on OATP1B1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 47 publications
3
36
1
Order By: Relevance
“…While this manuscript was in revision, Köck et al (2013) reported inhibition of OATP1B1, OATP1B3, and OATP2B1 transport function by silibinin A and B, which is in accordance with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…While this manuscript was in revision, Köck et al (2013) reported inhibition of OATP1B1, OATP1B3, and OATP2B1 transport function by silibinin A and B, which is in accordance with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Inhibition or stimulation of OATP2B1's function by drugs or foods could alter the pharmacokinetics of OATP2B1 substrates and potentially lead to adverse effects. Quite a few interactions between OATP2B1 and natural products have been reported in the literature (Fuchikami et al, 2006;Imanaga et al, 2011;Kock et al, 2013;Li et al, 2014;Mandery et al, 2010;Satoh et al, 2005;Shirasaka et al, 2013a,b;Tapaninen et al, 2010Tapaninen et al, , 2011Roth et al, 2011), suggesting that OATP2B1 could interact with a wide range of natural products. To identify more OATP2B1 modulators from natural products and to avoid potential adverse drug-drug and drug-food interactions, in this work the effects of 27 natural compounds and extracts on the function of OATP2B1 have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Roth et al (2011) reported that green tea catechins epicatechin gallate and epigallocatechin gallate significantly inhibited OATP2B1-mediated E3S uptake. Several flavonoids, silymarin flavonolignans, and antidiabetic drugs have also been reported to inhibit OATP2B1 in vitro (Bachmakov et al, 2008;Klatt et al, 2013;Kock et al, 2013;Li et al, 2014;Mandery et al, 2010). These reports demonstrated that OATP2B1 could interact with a wide range of natural products.…”
Section: Introductionmentioning
confidence: 93%
“…Silybin A 59 6 6.1 56 6 5.1 5.0 6 0.65 4.2 6 0.48 40 6 6.8 67 6 12 79 6 7.9 72 6 7.7 Silybin B 66 6 6.0 31 6 3.2 3.3 6 0.39 2.8 6 0.34 47 6 13 19 6 3.4 74 6 8.6 65 6 7.6 Silibinin 33 6 3.2 27 6 2.9 3.2 6 0.33 2.8 6 0.25 50 6 7.7 39 6 4.0 120 6 19 86 6 12 Silymarin 28 6 3.1 27 6 2.7 8.3 6 1.1 6.7 6 0.85 73 6 18 30 6 5.4 91 6 14 81 6 12 dmd.aspetjournals.org 3-fold, supporting these constituents as marker constituents predictive of the complex mixtures. Transport proteins, including organic anion-transporting polypeptides (OATPs), multidrug resistance proteins, and P-glycoprotein (P-gp) have been reported to contribute to the disposition of raloxifene, R4G, R6G (Jeong et al, 2004(Jeong et al, , 2005aChang et al, 2006;Trdan Lu sin et al, 2012a, b), and milk thistle flavonolignans (Miranda et al, 2008;Köck et al, 2013;Wlcek et al, 2013). The risk of interactions via milk thistle flavonolignan inhibition of OATP1B1-and OATP1B3-mediated hepatic uptake is believed to be low, based on limited systemic exposure (Köck et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Transport proteins, including organic anion-transporting polypeptides (OATPs), multidrug resistance proteins, and P-glycoprotein (P-gp) have been reported to contribute to the disposition of raloxifene, R4G, R6G (Jeong et al, 2004(Jeong et al, , 2005aChang et al, 2006;Trdan Lu sin et al, 2012a, b), and milk thistle flavonolignans (Miranda et al, 2008;Köck et al, 2013;Wlcek et al, 2013). The risk of interactions via milk thistle flavonolignan inhibition of OATP1B1-and OATP1B3-mediated hepatic uptake is believed to be low, based on limited systemic exposure (Köck et al, 2013). Similarly, silibinin may inhibit multidrug resistance protein 2-mediated canalicular efflux of raloxifene and its conjugates, but hepatocellular concentrations are likely too low to elicit clinically meaningful effects (Wlcek et al, 2013).…”
Section: Discussionmentioning
confidence: 99%